Impact of active fluid management on cardiac hemodynamics and mechanics in patients on maintenance hemodialysis - Paunić, Zoran; Dekleva-Manojlović, Milica; Marković-Nikolić, Nataša; Rančić, Nemanja; Dimković, Nada (Vojnosanitetski pregled, 2021)
Background/Aim. Overhydration (OH) and shortcomings of clinical assessment of so called „dry weight“ in hemodialysis (HD) patients are well known risk factors for high cardiovascular morbidity and mortality in this population. The purpose of this prospective randomized study was to investigate possible benefits of the active fluid management (AFM) guided by bioimpedance spectroscopy (BIS) on cardiac morphology, mechanics and function in chronic hemodialysis patients. Methods. The study lasted 9 months and 83 BIS naive patients were enrolled. Cardiac structural and functional characteristics were obtained using two dimensional Doppler echocardiography and global strains by speckle tracking modality. In addition, cardiac markers were measured. Results. Seventy three patients completed the study (38 in the active – AFM group and 35 in the control group). At the end of the study, the main structural change in the active group of patients was reduction of left ventricular mass index (from 62.81 ± 19.74 g/m2.7 to 57.74 ± 16.87g/m2..7; p = 0.007), while main functional improvements in this group were better left ventricular ejection fraction (LVEF; from 41.27 ± 9.26% to 43.95 ± 8.84%; p = 0.006) and fractional shortening (FS; 27.86 ± 5.94% to 29.86 ± 5.83%; p = 0.056) in accordance with improvement of radial left ventricular (LV) mechanics detected by higher global radial strain (GRS) (18.56 ± 10.24% to 21.79 ± 12.16%; p = 0.014). The diastolic function of patients in the control group worsened significantly, assessed as ratio of Doppler velocity of early diastolic filling of left ventricle – E, and average velocity of tissue Doppler measured at lateral part of the mitral annulus (e’ lateral; E/e’ lateral ratio 10.59 ± 5.00 to 11.12 ± 4.06; p = 0.036) and consecutively the right ventricular systolic pressure (RVSP) estimated indirectly by echocardiography: from 34.84 ± 10.18 mmHg to 38.76 ± 8.34 mmHg; p = 0.028. These functional changes were in correlation with significantly higher levels of N-terminal prohormone brain natriuretic peptide (NT-proBNP) in this group of patients [median and interquartile range (IQR): 5810.0 pg/mL (3339.0–15627.0 pg/mL) to 8024.0 pg/mL (4433.0–17467.0 pg/mL; p = 0.038)]. The improvement in the LV structure and function in the active group correlated with better relative overhydration (ROH) management in this group – the proportion of “critically” overhydrated patients decreased from 45% at the start to 24% at the end of study (p = 0.003). At the end of the study, there were 49% of post-dialysis “critically“ dehydrated patients in the control group. Proportion of anuric patients increased only in the control group (63% to 77%; p = 0.063). Conclusion. Active fluid management, guided by bioimpedance spectroscopy had positive impact on cardiac hemodynamics and mechanics in our study patients and could improve clinical decisions regarding their optimal weight and further clinical course. Further data from well designed studies are needed urgently.
Keywords: renal dialysis; ventricular function, left; echocardiography, doppler; biolectric impedance; biomarkers